Precariousness, Deteriorating Matter and Dispossessed Subjectivities: On the «Aesthetics of Decomposition» in Two Documentaries by Heddy Honigmann - Dajes Kaufman, Talía (2019)
This essay approaches the work of Peruvian- Dutch documentarian Heddy Honigmann by analyzing two of her films —Metal and Melancholy (1994) and Oblivion (2008)—, both set in Lima and centered on the precarious survival of its subjects. The text proposes to interpret each documentary’s visual language as the embodiment of what could be conceptualized as an «aesthetics of decomposition», thatis, the on-screen placement of objects undergoing a process of decay. I argue that, by pointing the camera toward these, the director exposes the economic and political circumstances that led to the gradual disintegration of individual and collective life conditions, as well as the erosion of the benefits previously enjoyed by middle class populations in Peru. By concentrating on the materiality of deteriorating objects, this article aims to connect Honigmann’s viewpoint with the effects that the implementation of neoliberalism may have over a paradigmatic subjectivity that can be conceived as dispossessed.